Sadd Al-Dzari'ah's Analysis Reviewed in Covid 19 Cases by The Government in Indonesia - Sudirman Suparmin (IHSA Institute, 2022)
The Covid-19 case, which has become a problem in the world and in Indonesia, is a common concern. In Indonesia, covid 19 cases with a percentage of 6.47 million, both confirmed cases, recovered cases, and deaths to active cases. Therefore, the purpose of this study is to find out the handling of Covid-19 by the Government in Indonesia, and to find out the concept of Sadd Al-Dzari'ah in the case of Covid 19 in Indonesia. The legal research method used is a type of normative juridical legal research by analyzing the case approach and the source of legal material used is the source of primary legal material studying the concept of Sadd Al-Dzari'ah and looking at data on covid 19 cases and skunder legal materials in the form of journals and other media related to this research. It is known that Indonesia has handled covid 19 cases as much as possible with various efforts, policies carried out by the government, which are ushered in making regulations and even forming teams etc. Then in the concept of Sadd Al-Dzari'ah is a concept born from the consideration of studies of legal considerations, especially for the benefit of the human ummah in line with the policies made by the government because it concerns the mashlahah of the human ummah.